Preventive detention: the ethical ground where politics and health meet. Focus on asylum seekers in Australia - Sheikh, M.; Macintyre, C.; Perera, Suvendrini (British Medical Journal Group, 2008)
Australia has a history of migration, especially during the wars in Europe, but many have forgotten the difficulties underlying asylum and wars endured by their forefathers. Preventive, indefinite detention of asylum seekers, most of whom are found to be genuine refugees, impinges on their human rights. The mental and physical health consequences of detention in this already traumatised group are significant, particularly in children. There are abundant studies to support this but, even as these studies continue to be done, asylum seekers languish in detention centres. To be fully addressed, the health implications of detention cannot be considered in isolation, but must be considered frankly and openly by health professionals in the broader historical and political context within which they occur. If we do not do this, we risk turning a blind eye to, or even condoning, human rights abuses.